Inequalities for Rational Functions with s-fold zeros at the Origin - Zargar, B A; Gulzar, M H; Akhter, Rubia (Sarajevo Journal of Mathematics, 2025)
In this paper, we establish some inequalities for rational functions with prescribed poles having s fold zeros at the origin. Our results generalize and refine the results of A. Aziz and W. M. Shah [2], A. Aziz and B. A. Zargar [3] and other known rational inequalities.